2009
DOI: 10.4012/dmj.28.227
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride release and recharge characteristics of denture base resins containing surface pre-reacted glass-ionomer filler

Abstract: The flexural strength, flexural modulus, and the amount of fluoride released from four experimental denture base resins containing 5, 10, 20 and 30 wt% surface pre-reacted glass-ionomer (S-PRG) filler added to the powder were evaluated. The mean flexural strength of the experimental resins, except the 30 wt%, and the flexural modulus of all the resins, complied with ISO 1567 requirements. In the 20 wt% resin, the amount of fluoride released in the initial phase was 1.88 μg/cm 2 /day, after which the level decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 27 publications
6
75
1
1
Order By: Relevance
“…Fluoride released by the S-PRG filler likely induces fluoroapatitelike precipitations in lesion bodies, inhibiting further demineralization 23) . In contrast to our finding, showing that IML was similar for S10 and S20, a study investigating the amount of fluoride ions released into deionized water over one week by experimental denture base resins containing 10 and 20 wt% S-PRG filler found that the 20 wt% resin released significantly more fluoride ions than the 10 wt% resin 24) . Also in this study, it was sure that temporary filling material containing 20% S-PRG filler released significantly more fluoride ions than that containing 10% S-PRG filler.…”
Section: Discussioncontrasting
confidence: 50%
“…Fluoride released by the S-PRG filler likely induces fluoroapatitelike precipitations in lesion bodies, inhibiting further demineralization 23) . In contrast to our finding, showing that IML was similar for S10 and S20, a study investigating the amount of fluoride ions released into deionized water over one week by experimental denture base resins containing 10 and 20 wt% S-PRG filler found that the 20 wt% resin released significantly more fluoride ions than the 10 wt% resin 24) . Also in this study, it was sure that temporary filling material containing 20% S-PRG filler released significantly more fluoride ions than that containing 10% S-PRG filler.…”
Section: Discussioncontrasting
confidence: 50%
“…In this study, we examined the early stages of fungal adhesion. A study using PMMA containing S-PRG filler showed that the amount of released fluoride decreased on the second day after immersion into distilled water, and further decreased to approximately one tenth at one week after immersion 31) . Furthermore, TC surface roughness increased with time 32) .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the effect of S-PRG filler on the inhibition of fungal adhesion will likely decrease over time. On the other hand, fluoride ions could be recharged into PMMA by immersion in a fluoride ionic solution 31) . Thus, the effects of ion recharge on fungal adhesion over longer periods should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The Shore hardness and rebound resilience of the material change depending on the S-PRG filler content. Kamijo et al have reported that an increase in S-PRG filler content correlates with a decrease in the durability and strength of the denture base-resin 30) . We attempted to determine the percentage of S-PRG filler that would be optimal for antimicrobial activity and the maintenance of shock absorption properties of mouthguards.…”
Section: Discussionmentioning
confidence: 99%